TINJAUAN NORMATIF TENTANG PERTANGGUNG JAWABAN TINDAK PIDANA PENCEMARAN NAMA BAIK DALAM SISTEM HUKUM INDONESIA - Krisnawan, Afi Bayu; Hartoyo, Hartoyo; Nasoetion, Dedi Wardana (Gapenas Publisher, 2025)
The massive use of social media has revolutionised the communication patterns of modern society, while also presenting serious challenges in the field of criminal law, particularly in relation to defamation. This phenomenon becomes even more complex when the legal norms that govern it, namely the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), do not provide an explicit definition of the elements of ‘insult’ or ‘defamation’ in the digital space. As a result, there is ambiguity in legal interpretation, leading to inconsistencies in the application of criminal sanctions by law enforcement agencies and courts. The surge in reports of defamation cases through social media is driven by high user accessibility and low digital literacy, which has a broad impact on the psychology of victims, loss of professional reputation, and even the disintegration of social relations. This study uses a normative juridical approach to critically examine the effectiveness of criminal sanctions against perpetrators of defamation through social media. The analysis is conducted on relevant court decisions, linked to the principles of criminal law, developments in information technology, and international human rights principles. This study also raises a comparative study with the German and Australian legal systems to evaluate the proportionality and accountability in imposing criminal sanctions for similar offences. The results of the study show that there is an urgency to harmonise regulations that are more adaptive to the digital context, in order to create substantive justice that not only protects individual reputation but also guarantees freedom of expression in a democratic country. These findings are expected to contribute strategically to the development of Indonesian criminal law that is responsive to the dynamics of digital communication and the need for balanced legal protection